WASTEWATER TREATMENT TECHNOLOGY FOR AGRICULTURAL IRRIGATION IN SPAIN - Bui Minh Tu; Nam Peng; Nguyen Thi Mai (Techno Agriculturae Studium of Research, 2025)
Water scarcity in Spain has become a major challenge for the agricultural sector, thus encouraging the use of treated wastewater as an alternative source of irrigation. This study aims to evaluate the effectiveness of wastewater treatment technology on agricultural productivity, environmental impact, and farmers’ income in Spain. The research method used is an experimental quantitative design with data collection from wastewater treatment plants, field tests on soil quality, as well as interviews and questionnaires to farmers in the research area. The results show that the use of treated wastewater increases crop yields by 10-15% and reduces the use of chemical fertilizers by 20%, without causing a negative impact on soil and groundwater quality. Farmers’ acceptance of this technology is also quite high, driven by real economic benefits. In conclusion, wastewater treatment technology in Spain has the potential to be a sustainable solution to the water crisis in the agricultural sector, although more research is needed to understand the long-term impact on the environment.